Widespread hepatitis C virus transmission network among people who inject drugs in Kenya - Matthew J. Akiyama; Yury Khudyakov; Sumathi Ramachandran; Lindsey R. Riback; Maxwell Ackerman; Mercy Nyakowa; Leonard Arthur; John Lizcano; Josephine Walker; Peter Cherutich; Ann Kurth (International Journal of Infectious Diseases, 2024)
Objectives: Hepatitis C virus (HCV) disproportionately affects people who inject drugs (PWID) worldwide. Despite carrying a high HCV burden, little is known about transmission dynamics in low- and middle-income countries. Methods: We recruited PWID from Nairobi and coastal cities of Mombasa, Kilifi, and Malindi in Kenya at needle and syringe programs. Next-generation sequencing data from HCV hypervariable region 1 were analyzed using Global Hepatitis Outbreak and Surveillance Technology to identify transmission clusters. Results: HCV strains belonged to genotype 1a (n = 64, 46.0%) and 4a (n = 72, 51.8%) and were mixed HCV/1a/4a (n = 3, 2.2%). HCV/1a was dominant (61.2%) in Nairobi, whereas HCV/4a was dominant in Malindi (85.7%) and Kilifi (60.9%), and both genotypes were evenly identified in Mombasa (45.3% for HCV/1a and 50.9% for HCV/4a). Global Hepatitis Outbreak and Surveillance Technology identified 11 transmission clusters involving 90 cases. Strains in the two largest clusters (n = 38 predominantly HCV/4a and n = 32 HCV/1a) were sampled from all four cities. Conclusions: Transmission clusters involving 64.7% of cases indicate an effective sampling of major HCV strains circulating among PWID. Large clusters involving 77.8% of strains from Nairobi and Coast suggest successful introduction of two ancestral HCV/1a and HCV/4a strains to PWID, with widely spread progeny. The disruption of the country-wide transmission network is essential for HCV elimination.